Spin–Orbit and Coulomb Effects in Single‐Layered Ruthenates. Issue 11 (27th June 2018) - Zhang, Guoren; Pavarini, Eva
Abstract : Single‐layered ruthenates continue to surprise us decades after their discovery. Here we briefly review some recent advances in the understanding of their electronic properties. They have been obtained via the LDA + DMFT method, the state‐of‐the‐art approach for strongly correlated systems. In particular, we discuss the effects of the spin–orbit interaction and its interplay with the crystal field in the presence of electron–electron repulsion. We focus on the Fermi surface of Sr2 RuO4 and the metal–insulator transition in Ca2− x Sr x RuO4 . Abstract : Single‐layered ruthenates with the Ruddlesden–Popper structure have been intensively investigated since their discovery. Their remarkable properties range from unconventional (perhaps topological) superconductivity to a Mott phase with pseudo‐Goldstone modes and a possible Higgs mode. In this Review, the authors give a short introduction to recent theoretical advances in understanding the electronic and magnetic properties of these materials. The article focuses on spin–orbit and crystal field effects and their interplay with electronic correlations.